Dynamics, stability, and foresight in the Shapley-Scarf housing market - Yoshio Kamijo; Ryo Kawasaki (Fondazione Eni Enrico Mattei (FEEM), 2009)
While most of the literature starting with Shapley and Scarf (1974) have considered a static exchange economy with indivisibilities, this paper studies the dynamics of such an economy. We find that both the dynamics generated by competitive equilibrium and the one generated by weakly dominance relation, converge to a set of allocations we define as strictly stable, which we can show to exist. Moreover, we show that even when only pairwise exchanges between two traders are allowed, the strictly stable allocations are attained eventually if traders are sufficiently farsighted.
Keywords: D78; C71; 330; Indivisible Goods Market; Dynamics; Competitive Allocation; Strict Core; Foresight; Stable Set